Climate variability and the outbreaks of cholera in Zanzibar, East Africa: A time series analysis - Reyburn, R.; Kim, D.; Emch, M.; Khatib, A.; Von Seidlein, L.; Ali, Mohammed (The American Society of Tropical Medicine and Hygiene, 2011)
Global cholera incidence is increasing, particularly in sub-Saharan Africa. We examined the impact of climate and ocean environmental variability on cholera outbreaks, and developed a forecasting model for outbreaks in Zanzibar. Routine cholera surveillance reports between 1997 and 2006 were correlated with remotely and locally sensed environmental data. A seasonal autoregressive integrated moving average (SARIMA) model determined the impact of climate and environmental variability on cholera. The SARIMA model shows temporal clustering of cholera. A 1° C increase in temperature at 4 months lag resulted in a 2-fold increase of cholera cases, and an increase of 200 mm of rainfall at 2 months lag resulted in a 1.6-fold increase of cholera cases. Temperature and rainfall interaction yielded a significantly positive association ( P < 0.04) with cholera at a 1-month lag. These results may be applied to forecast cholera outbreaks, and guide public health resources in controlling cholera in Zanzibar. Copyright © 2011 by The American Society of Tropical Medicine and Hygiene.